NPR : the trials and triumphs of National Public Radio - McCauley, Michael P., 1958- (Columbia University Press, 2005)
The people who shaped America's public broadcasting system thought it should be ""a civilized voice in a civilized community""?a clear alternative to commercial broadcasting. This book tells the story of how NPR has tried to embody this idea. Michael P. McCauley describes NPR's evolution from virtual obscurity in the early 1970s, when it was riddled with difficulties?political battles, unseasoned leadership, funding problems?to a first-rate broadcast organization. The book draws on a wealth of primary evidence, including fifty-seven interviews with people who have been central to t